Analisis Fenomena Weekend Effect dan Monday Effect terhadap Return Saham Perusahaan - Haryadi, Bayu; Dara, Siti Ruhana (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2024)
Abstract: The research aims to determine the impact of the Monday effect and Weekend effect on the daily stock Returns of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange from April 2020 to April 2021. The research analysis method used multiple linear regression with the assistance of IBM SPSS Statistics 26 software. A total of 11 companies from the sub-sector were selected as the population for this study, and after applying purposive sampling method, a sample of 9 companies was obtained from the total population. The daily stock Returns calculation in this research was based on the closing prices. The study found that the Monday effect variable had no significant partial impact on stock Returns. However, the Weekend effect variable had a significant partial impact on stock Returns, and both the Monday effect and Weekend effect variables together had an impact on daily stock Returns. Keywords: Stock-Return, Monday-effect, Weekend-effect, Market-anomaly